Anlotinib plus chemotherapy for T790M‐negative EGFR‐mutant non‐sqNSCLC resistant to TKIs: A multicenter phase 1b/2 trial. Issue 24 (8th November 2022) - Li, Juan; Tian, Yuke; Zheng, Min; Ge, Jun; Zhang, Jiliang; Kong, Dejun; Chen, Mei; Yu, Ping
Abstract: Background: This multicenter phase 1b/2 trial aimed to explore the maximum tolerated dose (MTD), activity, and safety of anlotinib plus chemotherapy in patients with T790M‐negative epidermal growth factor receptor ( EGFR )‐mutant advanced nonsquamous non‐small cell lung cancer (NSCLC) after resistance to first‐ or second‐generation EGFR tyrosine kinase inhibitors (TKIs). Methods: In the phase 1b stage, patients received anlotinib (8/10/12 mg, days 1–14) combined with cisplatin (75 mg/m 2, day 1) or carboplatin (AUC = 5, day 1) plus pemetrexed (500 mg/m 2, day 1) for a 3‐week cycle based on a 3 + 3 dose‐escalation design. In the phase 2 single‐arm stage, anlotinib was administered at MTD combined with platinum plus pemetrexed for four cycles, followed by anlotinib maintenance therapy. The primary endpoint of the phase 2 stage was progression‐free survival (PFS). Results: The study was prematurely terminated due to slow accrual after 19 patients had been enrolled between January 18, 2019, and March 21, 2021. The MTD of anlotinib was 12 mg. The median PFS was 5.75 (95% confidence interval, 4.37–7.52) months. The objective response rate was 47.4% (95% confidence interval, 24.5%–71.1%). In the 12 mg group, seven (58.3%) patients experienced grade 3–4 treatment‐related adverse events, and the most common ones were hypertension (6 [50.0%]), decreased platelet count (2 [16.7%]), and hypertriglyceridemia (1 [8.3%]). No treatment‐related deaths occurred. Conclusion: Anlotinib plus platinum and pemetrexed showed promising antitumor activity with manageable toxicity in patients with T790M‐negative EGFR ‐mutant advanced nonsquamous NSCLC after progression on first‐ or second‐generation EGFR TKIs. Abstract : Patients with T790M‐negative EGFR ‐mutant advanced NSCLC received anlotinib plus platinum‐based chemotherapy after resistance to first‐ or second‐generation EGFR TKIs. The maximum tolerated dose (MTD) of anlotinib was 12 mg, and the median PFS was 5.75 (95% CI: 4.37–7.52) months. This combination therapy might be a potential alternative option as a second‐line treatment.